A computational approach to investigate optimal cutting speed configurations in rotational needle biopsy cutting soft tissue. Issue 1 (2nd January 2019) - Lin, Chi-Lun; Lan, Guan-Jhong
Abstract: The rotational cutting method has been used in needle biopsy technologies to sample tough tissues, such as calcifications in the breast. The rotational motion of the needle introduces shear forces to the cutting surface such that the cutting force in the axial direction is reduced. As a result, tissue samples with large volume and better quality can be obtained. In order to comprehensively understand the effect of the needle rotation to the axial cutting force under a wide range of the needle insertion speed, this paper demonstrates a computational approach that incorporates the surface-based cohesive behavior to simulate a rotating needle cutting soft tissue. The computational model is validated by comparing with a cutting test dataset reported in the literature. The validated model is then used to generate response surfaces of the axial cutting force and torque in a large parameter space of needle rotation and insertion speeds. The results provide guidelines for selecting optimal speed configurations under different design situations.